2021
DOI: 10.23950/jcmk/11037
|View full text |Cite
|
Sign up to set email alerts
|

Network analysis of nursing publications in the COVID 19 era

Abstract: Objective: COVID 19, which affects all areas of life, is perhaps one of the most studied subjects in the field of medicine, and the number of global publications is increasing day by day. The nursing profession and practices have also been directly affected by this rapid stream of broadcasts. The study was planned to examine in detail the studies on 'COVID and nursing' and to guide the studies to be planned in the future.Material and methods: In our study, the Web of Science (WOS) database was scanned to searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…As mostly previously studies [11][12][13][14][15][16][17], our study showed that the majority of articles from USA. This may due to research findings and large number of researchers in USA.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…As mostly previously studies [11][12][13][14][15][16][17], our study showed that the majority of articles from USA. This may due to research findings and large number of researchers in USA.…”
Section: Discussionsupporting
confidence: 84%
“…Bibliometric analysis which is social science study area, has been started to use in medical area in recent years. As different researchers made this analysis on different medical topics, it became easier to give way to perspective for future studies [11][12][13][14][15][16]. Pubmed, The Web of Science (WOS) and Scopus databases are mostly common databases mainly preferred in bibliometric analyses [11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Web of Science Core Collection (WoSCC) and Scopus databases are frequently used databases in bibliometric analysis. With this analysis method, publications can be analyzed using many methods such as visualization, citation analysis, mapping techniques [10][11][12]. Ready-to-use databases can be used, as well as database mining can be preferable.…”
Section: Discussionmentioning
confidence: 99%
“…Ready-to-use databases can be used, as well as database mining can be preferable. With this quantitative method, parameters such as the the leading country in a topic, authors, publication years, and contents of the publications [8][9][10][11][12][13][14]. We conducted a bibliometric study with the Scopus database, as it is the widest range on publications.…”
Section: Discussionmentioning
confidence: 99%